Modern day myths in Neil Gaiman's American Gods - Mohamed Roslan, Syed Mikhail; Noor, Rohimmi; Jujar Singh, Hardev Kaur (Human Resource Management Academic Research Society, 2020)
This thesis will focus on the function of multi-mythology in contemporary literature especially the fantasy genre. In particular, this thesis analyses American Gods by Neil Gaiman by drawing upon Claude Lévi-Strauss' and Vladmir Propp's structuralist ideas and to see how the original myths were substituted, modulated or transfigured to be presented as metamyth or myth transformed. In particular, I will argue that American Gods is a demonstration of Joseph Campbell’s theory of the monomyth from the The Hero with a Thousand Faces. The findings of this study may encourage future researchers into analysing other texts and finding similar themes to fill in the gaps of existing knowledge in mythology.